2015
DOI: 10.2337/db14-1933
|View full text |Cite
|
Sign up to set email alerts
|

DAPK2 Downregulation Associates With Attenuated Adipocyte Autophagic Clearance in Human Obesity

Abstract: Adipose tissue dysfunction in obesity has been linked to low-grade inflammation causing insulin resistance. Transcriptomic studies have identified death-associated protein kinase 2 (DAPK2) among the most strongly downregulated adipose tissue genes in human obesity, but the role of this kinase is unknown. We show that mature adipocytes rather than the stromal vascular cells in adipose tissue mainly expressed DAPK2 and that DAPK2 mRNA in obese patients gradually recovered after bariatric surgery–induced weight l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 53 publications
6
58
0
Order By: Relevance
“…In fact, autophagy was induced in adipose tissue from obese individuals, and inhibition of autophagy increased expression of the pro-inflammatory genes IL-1, IL-6 and IL-8 both in adipocytes and adipose tissue explants of obese individuals compared to non-obese controls (51). Consistent with these observations, in adipocytes isolated from obese patients recovering from bariatric surgery-induced weight loss, both DAPK2 expression and autophagic clearance were markedly increased and adipocyte size was proportionally reduced post-surgery compared to the adipocytes from same patients prior to surgery (52). Consistent with these observations, in adipocytes isolated from obese patients recovering from bariatric surgery-induced weight loss, both DAPK2 expression and autophagic clearance were markedly increased and adipocyte size was proportionally reduced post-surgery compared to the adipocytes from same patients prior to surgery (52).…”
Section: Downloaded Fromsupporting
confidence: 69%
“…In fact, autophagy was induced in adipose tissue from obese individuals, and inhibition of autophagy increased expression of the pro-inflammatory genes IL-1, IL-6 and IL-8 both in adipocytes and adipose tissue explants of obese individuals compared to non-obese controls (51). Consistent with these observations, in adipocytes isolated from obese patients recovering from bariatric surgery-induced weight loss, both DAPK2 expression and autophagic clearance were markedly increased and adipocyte size was proportionally reduced post-surgery compared to the adipocytes from same patients prior to surgery (52). Consistent with these observations, in adipocytes isolated from obese patients recovering from bariatric surgery-induced weight loss, both DAPK2 expression and autophagic clearance were markedly increased and adipocyte size was proportionally reduced post-surgery compared to the adipocytes from same patients prior to surgery (52).…”
Section: Downloaded Fromsupporting
confidence: 69%
“…The anatomic localization of adipocytes may determine a different response in autophagic flux in obesity conditions. Of note, Soussi et al (125) have recently shown an attenuation of autophagy in subcutaneous adipose tissue of patients with obesity in contrast with increased autophagy observed in dysfunctional visceral adipocytes.…”
Section: Autophagy In Adipose Tissuementioning
confidence: 95%
“…DAPK2 regulates obesity-related attenuated autophagy in adipocytes -DAPK2 downregulation associates with attenuated adipocyte autophagic clearance in human obesity (Soussi H et al, 2015).…”
Section: Obesitymentioning
confidence: 99%